2000
DOI: 10.1063/1.372504
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ta on the magnetic thickness of permalloy (Ni81Fe19) films

Abstract: The effect of Ta and Ta/Cu seed layers, and Ta and Cu cap layers on the effective magnetic thickness of ultrathin permalloy (Ni81Fe19) was investigated for MRAM applications. The films were deposited by Ion Beam Deposition. The magnetic moment of each as-deposited permalloy film was measured using a B-H looper and a SQUID magnetometer. The films were further annealed at either 525 K for 1/2 h or 600 K for 1 h to study the effect of thermally driven interdiffusion on the magnetic moment of the permalloy film. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 2 publications
8
34
0
Order By: Relevance
“…2), and previously, we speculated that differences in the deposition sequence play a key role in formation of the interfacial structure and interlayer diffusion during annealing [3]. For instance, CoFe has a larger surface free energy than IrMn, which results in blending of CoFe with the IrMn layer during deposition, thereby creating relatively thick, magnetically dead layers [10][11][12]. A comparison of the interfaces of CoFe/IrMn in the B-SV and IrMn/CoFe in the T-SV in the as-deposited state shows that the two interfaces differ energetically.…”
Section: Resultsmentioning
confidence: 87%
“…2), and previously, we speculated that differences in the deposition sequence play a key role in formation of the interfacial structure and interlayer diffusion during annealing [3]. For instance, CoFe has a larger surface free energy than IrMn, which results in blending of CoFe with the IrMn layer during deposition, thereby creating relatively thick, magnetically dead layers [10][11][12]. A comparison of the interfaces of CoFe/IrMn in the B-SV and IrMn/CoFe in the T-SV in the as-deposited state shows that the two interfaces differ energetically.…”
Section: Resultsmentioning
confidence: 87%
“…(10), where X indicates the Ni composition in NiFe and d indicates the deposition thickness of NiFe. Three kinds of capping layers were prepared: Ta(5), Al(0.7)-oxide/Ta(5), and Ru(3)/ Ta (5). We named the samples according to the capping layers, i.e., ''Ta cap'', ''AlO cap'', and ''Ru cap'', respectively.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] Although attention should be given to MRAM write operations, the thermal robustness of the switching field (H sw ) in the MTJs of MRAM cell structures has not been adequately studied. The magnetic properties of ultrathin NiFe layers sandwiched between Ta or Cu under and capping layers have been investigated and the reaction at the NiFe/Ta interface was shown to create a thick magnetic dead layer, 5,6) which can interfere with the H sw of MTJs after high-temperature treatments. On the other hand, we have already reported that a thin Al-oxide (AlO) layer can prevent interdiffusion between the NiFe and CoFe layers even after annealing at 400 C, 4) and we briefly demonstrated the same effect for AlO between NiFe and Ta layers, leading to a large improvement in the magnetic properties of NiFe after annealing at 400 C. 7) However, to date, the overall effect of capping layer materials with magnetoresistive properties in MTJ devices has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A bilayer of 2 nm tantalum (Ta) and 10 nm NiFe was sputter deposited on an oxidized Si wafer with $ 300 nm thick SiO 2 . Hence, Ta only served as a the seed layer 70,71 to increase the adhesion of NiFe to the substrate. Electrochemical Au deposition occurred on NiFe aged for more than one month at room temperature.…”
Section: Ability To Arbitrarily Choose Metal Electrodesmentioning
confidence: 99%